Replication of biotinylated human immunodeficiency viruses - Belshan, Michael (2010)
Previous work demonstrated recently the adaptation of the E. coli biotin ligase BirA - biotin acceptor sequence (BAS) labeling system to produce human immunodeficiency virus type 1 viruses with biotinylated integrase (NLXIN(B)) and matrix (NLXMA(B)) proteins (Belshan et al., 2009). This report describes the construction of an HIV permissive cell line stably expressing BirA (SupT1.BirA). Consistent with the results in the previous report, NLXMA(B) replicated similar to wild-type levels and expressed biotinylated Gag and MA proteins in the SupT1.BirA cells, whereas the replication of NLXIN(B) was reduced severely. Three additional HIV type 2 (HIV-2) viruses were constructed with the BAS inserted into the vpx and vpr accessory genes. Two BAS insertions were made into the C-terminal half of the Vpx, including one internal insertion, and one at the N-terminus of Vpr. All three viruses were replication competent in the SupT1.BirA cells and their target proteins biotinylated efficiently and incorporated into virions. These results demonstrate the potential utility of the biotinylation system to label and capture HIV protein complexes in the context of replicating virus.